Manajemen Hubungan Masyarakat di SMK Nurul Islam - Mufidah, Hidayatul (Lembaga Intelektual Muda (LIM) Maluku, 2022)
Quality educational institutions are educational institutions that meet national education standards. To achieve quality education, a school requires management, one of which is public relations management. Nurul Islam Vocational School is said to have good public relations management, which can be seen from its cooperative relationships with several companies and the community. The research used is qualitative research. Using observation, interview and documentation data collection methods. The data sources used in this research are primary and secondary data. The respondents interviewed were the principal, deputy head of public relations, department heads and teachers. In terms of data analysis techniques, there are several data analysis techniques carried out, namely, data collection, data reduction, data presentation to arrive at a conclusion on the data. The results of this research describe, 1) public relations management at Nurul Islam Vocational School carries out four functions of management itself, namely planning public relations to be implemented, organizing them according to the plan, implementing and even controlling or controlling them. 2) The supporting factors in public relations management are as follows, the curriculum that has been designed at Nurul Islam Vocational School. Meanwhile, the inhibiting factors are costs and facilities